"Am I Trans Enough?": A Hermeneutical Phenomenological Investigation into Transgender Gender Identity - Kim, Chloe Seongeun (Université d'Ottawa | University of Ottawa, 2024)
Previous medical and sociological studies have attempted to explain how transgender people develop their identity, while at the same time, feminist and sociology scholars discussed socially constructed nature of gender. Yet, in arguing that there is no essential characteristic of one's gender, these studies offer unsatisfying answers as to how trans people come to know their gender. To explore this phenomenon, a series of interviews were conducted with six transgender and non-binary adults in Ottawa, guided by hermeneutical phenomenology. The results show that knowing one's gender identity is exploring one's desires guided by feeling of joy. These findings, and a subsequent analysis on a praxis of joy, suggest a way to validate transgender identities as something "real," while also avoiding reification of gender categories, by centring desires as core structure of gender identity.
Keywords: transgender; gender; gender identity; phenomenology; desire; joy; 2SLGBTQ+; queer; Deleuze; Butler